Environmental long read amplicons of soil fungi across Podzol soil profile - Anna Rosling (Uppsala University, 2022)
Soil samples were collected in mid-October 2013 from Ivantjärnsheden field station in Jädraås (60°49‘N, 16°30’E, altitude 185 m), a well-documented field site in central Sweden (Persson, 1980) with Pinus sylvestris L. overstory and an understory of ericaceous dwarf shrubs (Calluna vulgaris (L.) Hull and Vaccinium vitis-ideae L.) and mosses (Dicranum majus Turner and Pleurozium schreberi (Bridel) Mitten). To account for small-scale variability in soil fungal communities we collected 5 soil cores (5 cm diameter and 15 cm deep) in each of 12 plots in the since terminated experiment IhII (9802) (Axelsson & Bråkenhielm, 1980). After visually dividing the plot into four quadrats one core were taken from the middle of each quadrat and from the middle of the plot after peeling back the top shrub and moss layer (incl. most of the litter layer). Soil cores were separated into visually distinct podzol soil layers: organic soil (O), mineral elluvial soil (E) and mineral illuvial soil (B) before pooling the layers for each plot. From each composite soil sample two sub-samples of approximately 0.5 g wet weight were collected for DNA extraction. Approximately 1500 bp of the rDNA from all soil DNA extracts was amplified using the primer set ITS1F (Gardes & Bruns, 1993) and LR5 (Hopple Jr & Vilgalys, 1994). A total of 5, 8 and 3 samples successfully amplified for O, E and B horizons, respectively (Table S1). PCR products from the separate soil horizons were pooled to generate three amplicon libraries (SwO, SwE and SwB) for sequencing at SciLifeLab/NGI (Uppsala, Sweden) on a PacBio RS II system (Pacific Biosciences, Menlo Park, CA, USA).
This dataset was published via the SBDI ASV portal.
Keywords: Occurrence; OCCURRENCE; Biological Sciences; Biologi